Diffraction of real and virtual photons in a pyrolytic graphite crystal as source of intensive quasimonochromatic X-ray beam - Bogomazova E. A.; Kalinin B. N.; Padalko D. V.; Potylitsyn A. P. Alexander Petrovich; Sharafutdinov A. F.; Vnukov I. E.; Naumenko G. A. Gennadiy Andreevich (2003, 2003)
Title screen